HYDROGRAPHY OF THE INSHORE WATERS OF MADRAS COAST FOR THE PERIOD JANUARY 1973 TO MARCH 1975 - Muthuswamy, S (Indian Journal of Fisheries, 2011)
Wa,ter samples were collected from the inshore surface water’s off Madras dty, wher’e the depth ranged fJ’OIU 20 to 30 metres, ,and the changes in salinity, pH, dissolved-oxygen content, phosphate, nitrite, silicate and nit.faJte were monitered fr’Om J’anuary 1973 to Ma:roh 1975. Observations on the sea surface temperature were made from an arela adjoining ,the Madras Harbour. The variations observed were subje,caed 1;0 smoothing analysis and are depicted in figures 1 and 2.